HIV trends and disparities by gender and urban-rural residence among adolescents in sub-Saharan Africa - Réka Maulide Cane; Dessalegn Y. Melesse; Nkomba Kayeyi; Adom Manu; Yohannes Dibaba Wado; Aluisio Barros; Ties Boerma (BMC, 2021)
Abstract Background In sub-Saharan Africa HIV transmission is a major challenge in adolescents, especially among girls and those living in urban settings. Major international efforts have aimed at reducing sexual transmission of HIV. This analysis aims to assess the trends in HIV prevalence by gender in adolescents, as well as urban-rural disparities. Methods HIV prevalence data at ages 15-19 years were obtained for 31 countries with a national survey since 2010 and for 23 countries with one survey circa 2005 and a recent survey circa 2015. Country medians and average annual rates of changes were used to summarize the trends for two subregions in sub-Saharan Africa, Eastern and Southern Africa and West and Central Africa, which largely correspond with higher and lower HIV prevalence countries. Data on HIV incidence at ages 15-24 and prevalence at 5-9 and 10-14 years were reviewed from 11 recent national surveys. Trends in urban-rural disparities in HIV prevalence and selected indicators of sexual and HIV testing behaviours were assessed for females and males 15-24 years, using the same surveys. Results HIV prevalence among girls 15-19 years declined in eastern and Southern Africa from 5.7 to 2.6% during 2005-2015 (country median), corresponding with an average annual rate of reduction of 6.5% per year. Among boys, the median HIV prevalence declined from 2.1 to 1.2%. Changes were also observed in West and Central Africa where median HIV prevalence among girls decreased from 0.7 to 0.4% (average annual rate of reduction 5.9%), but not for boys (0.3%). Girl-boy differences at 10-14 years were small with a country median HIV of 1.0% and 1.3%, respectively. Urban females and males 15-24 had at least 1.5 times higher HIV prevalence than their rural counterparts in both subregions, and since the urban-rural declines were similar, the gaps persisted during 2005-2015. Conclusions HIV prevalence among adolescents declined in almost all countries during the last decade, in both urban and rural settings. The urban-rural gap persisted and HIV transmission to girls, but not boys, is still a major challenge in Eastern and Southern African countries.